E-SAMSAT IN REALIZING PUBLIC SERVICES AT THE SAMSAT OFFICE IN GOWA DISTRICT - Rianti, Rianti; Nur, Andi Cudai; Guntur, Muhammad; Rukmana, Novayanti Sopia (Jurnal Aktor, 2025)
This study  aims to determine  the quality of e-Samsat in realizing public services at the Samsat Office in Gowa Regency and to determine the quality of public services from the e-Samsat public service system in the Samsat Office in Gowa Regency.  This research uses a qualitative approach with descriptive methods. Data collection was carried out by field observations, interviews and documentation.  Data analysis techniques use data condensation,  data  presentation  and conclusion.  The results of this study indicate that the success  of e-Samsat  in realizing  public services  at the Samsat Office in Gowa Regency has not been optimally successful. This can be seen through three research  indicators. The successful indicator is Accountability with a clear type of service when using the e-Samsat  service.  Responsiveness  and Responsibility indicators that have not been successful in implementing this e -Samsat service system. The e-Samsat service  system at the Gowa Regency  Samsat office  has not been able to create quality services.